Advanced cardiac life support : a guide for nurses - Jevon, Philip; Pooni, J. S. [ (Jagtar Singh)] (Wiley-Blackwell, 2010)
* An evidence-based approach to emergency care based on the latest Resuscitation guidelines * A succinct yet comprehensive guide to the management of cardiac arrest * Written by an experienced resuscitation training offer who is also a qualified nurse and former CCU Charge Nurse.